Transcriptomic Profile of Mycobacterium smegmatis in Response to an Imidazo[1,2-b][1,2,4,5]tetrazine Reveals Its Possible Impact on Iron Metabolism - Vatlin, Aleksey A.; Shitikov, Egor A.; Shahbaaz, Mohd; Bespiatykh, Dmitry A.; Klimina, Ksenia M.; Christoffels, Alan; Danilenko, Valery N.; Maslov, Dmitry A. (Frontiers in Microbiology, 2021)
Tuberculosis (TB), caused by the Mycobacterium tuberculosis complex bacteria, is one of the most pressing health problems The development of new drugs and new therapeutic regimens effective against the pathogen is one of the greatest challenges in the way of tuberculosis control. Imidazo[1,2-b][1,2,4,5]tetrazines have shown promising activity against M. tuberculosis and M. smegmatis strains. Mutations in MSMEG_1380 lead to mmpS5-mmpL5 operon overexpression, which provides M. smegmatis with efflux-mediated resistance to imidazo[1,2-b][1,2,4,5]tetrazines, but the exact mechanism of action of these compounds is remaining unknown. To assess the mode of action of imidazo[1,2-b][1,2,4,5]tetrazines, we analyzed the transcriptomic response of M. smegmatis to three different concentrations of 3a compound: 1/8 , 1/4 , and 1/2  MIC. Six groups of genes responsible for siderophore synthesis and transport were upregulated in a dose-dependent manner, while virtual docking revealed proteins involved in siderophore synthesis as possible targets for 3a. Thus, we suggest that imidazo[1,2-b][1,2,4,5]tetrazines may affect mycobacterial iron metabolism.